Congratulation by the Director of Center of Excellence of Healthcare and Pharmacy Specialists - Juozas Ruolia, Director of Center of Excellence of Healthcare and Pharmacy Specialists (Slauga. Mokslas ir praktika, 2020)
Sveikatos priežiūros ir farmacijos specialistų kompetencijų centro direktoriaus sveikinimas.